1960
DOI: 10.5006/0010-9312-16.5.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Drawing On Hydrogen Behavior in Steel

Abstract: Hydrogen absorption by and the desorption rate of hydrogen from steel were studied as a function of cold work from 0 to 55.4 percent reduction using cold-drawn capped and killed SAE 1020 steel. Increased cold work increased the hydrogen solubility in these steels. Hydrogen desorption rate increased with increasing cold work until a maximum was reached at some point below 30.5 percent reduction. With further reduction, the desorption rate decreased. 3.7.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1964
1964
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…There is a general agreement as to the effect of cold working on hydrogen permeation. Plastic straining increases the number of dislocations that act as hydrogen traps, increasing hydrogen solubility and resulting in a consequent decrease in D eff (Bockris, Beck, Genshaw, Subramanyan, & Williams, 1971;Bockris, McBreen, & Nanis, 1965;Choo & Lee, 1983;Dietzel, Pfuff, & Juiffs, 2006;Fallahmohammadi et al, 2014a,b;Ha, Ai, & Scully, 2014;Hirth, 1980;Hudson & Straagand, 1960;Kumnick, 1980;Olden, Senumstad Hauge, & Magne Akselsen, 2012;Oriani, 1970;Radhakrishnan & Shreir, 1967;Xie & Hirth, 1982).…”
Section: Hydrogen Diffusionmentioning
confidence: 99%
“…There is a general agreement as to the effect of cold working on hydrogen permeation. Plastic straining increases the number of dislocations that act as hydrogen traps, increasing hydrogen solubility and resulting in a consequent decrease in D eff (Bockris, Beck, Genshaw, Subramanyan, & Williams, 1971;Bockris, McBreen, & Nanis, 1965;Choo & Lee, 1983;Dietzel, Pfuff, & Juiffs, 2006;Fallahmohammadi et al, 2014a,b;Ha, Ai, & Scully, 2014;Hirth, 1980;Hudson & Straagand, 1960;Kumnick, 1980;Olden, Senumstad Hauge, & Magne Akselsen, 2012;Oriani, 1970;Radhakrishnan & Shreir, 1967;Xie & Hirth, 1982).…”
Section: Hydrogen Diffusionmentioning
confidence: 99%
“…Additionally, the as-quenched martensite contains the lowest hydrogen diffusivity due to the dense microstructure. [19][20][21] On the contrary, tempered bainite or martensite has the best resistance against the hydrogen-induced ductility loss, while the pearlitic structure performs in between. 22 In another study on the hydrogen diffusivity of different microstructural features, Chan and Charles 23 found that martensite demonstrated the highest hydrogen solubility together with the lowest hydrogen diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…The main ones are temperature, alloy composition, crystalline structure and substructure. Nevertheless, the presence of H in metals and specifically in steels is not desired in most of the cases, since H alters considerably the mechanical-metallurgic properties of these materials with the possibility of fracture [9][10][11][12][13][14]. The most typical damage caused by H in steel is embrittlement.…”
Section: Introductionmentioning
confidence: 99%